Accounting and Valuation of Bearer Plants in Cameroon: Array - Rotimi, Mathew; Doorasamy, Mishelle; Rajaram, Rajendra; Kebbi, Metutu Joseph (EuroEconomica, 2022)
This research essay empirically assessed the accounting and valuation framework adopted for bearer plants, such as bananas in Cameroon. The study adopted a qualitative research approach to assess the accounting and valuation process for bananas as a type of bearer plant in Cameroon. The study utilized both a secondary analysis and a survey to evaluate and decipher how the Cameroon Development Corporation (CDC) accounts and values the bananas that it produces and exports to the world. From the secondary analysis, the study found the major global producers/exporters of bananas and ranks Cameroon at a global level. Furthermore, the findings of the field survey conducted among the relevant stakeholders made several novel and remarkable findings on how the CDC accounts for and values its bananas. This study contributes to the existing knowledge by seeking to appraise the accounting and valuation framework adopted for bearer plants such as bananas. Specifically, the study found, contrary to the earlier studies, that bananas are adequately accounted for and fairly valued. Nonetheless, the study recommends that CDC and GEL’s own internal assessments should not become a benchmark for accounting interpretation. Furthermore, it recommends that operational cash flows should be compiled monthly to facilitate auditing consistency.